2013
DOI: 10.1038/jid.2012.266
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miR-145 as a Key Regulator of the Pigmentary Process

Abstract: The current treatments for hyperpigmentation are often associated with a lack of efficacy and adverse side effects. We hypothesized that microRNA (miRNA)-based treatments may offer an attractive alternative by specifically targeting key genes in melanogenesis. The aim of this study was to identify miRNAs interfering with the pigmentary process and to assess their functional role. miRNA profiling was performed on mouse melanocytes after three consecutive treatments involving forskolin and solar-simulated UV (ss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 41 publications
(42 reference statements)
2
114
0
2
Order By: Relevance
“…Thus, it is possible that loss of miRNAs in melanocytes could cause pigmentary changes resulting in alterations in coat color. Indeed, several melanocyte miRNAs are linked to either melanocyte survival or pigmentation processes (47)(48)(49)(50)(51). Therefore, we hypothesized that the link between coat color and the severity of retinal degeneration might arise from Cre expression patterns that vary from animal to animal but remain consistent within the pigmentary cells of the same animal.…”
Section: Maturementioning
confidence: 99%
“…Thus, it is possible that loss of miRNAs in melanocytes could cause pigmentary changes resulting in alterations in coat color. Indeed, several melanocyte miRNAs are linked to either melanocyte survival or pigmentation processes (47)(48)(49)(50)(51). Therefore, we hypothesized that the link between coat color and the severity of retinal degeneration might arise from Cre expression patterns that vary from animal to animal but remain consistent within the pigmentary cells of the same animal.…”
Section: Maturementioning
confidence: 99%
“…SIRT1 has been shown to regulate stress-activated MAPK pathway via Akt and ASK1 in vitiligo keratinocytes (Becatti et al 2014). Previous studies have demonstrated the influence of miR-145 on the genes involved in the pigmentation process (Dynoodt et al 2013). The genes targeted by miR-145 also regulate MAPK pathway along with JNK and TGFB signaling pathway and are related to the functional groups that might indirectly influence cellular processes in vitiligo wherefore they interfere with melanocytes function and viability (Šahmatova et al 2016) suggesting the role of both miR-9 and miR-145 in the destruction of melanocytes in vitiligo.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 2.88 × 10 5 human infected melanocytes were seeded onto each dermal layer for 24 h and 7.2 × 10 5 HaCaT cells were seeded onto the melanocytes to construct the epidermis. The OTC was cultured for 2 d and then raised to the air-liquid interface.…”
Section: Human Melanocyte and Fibroblast Isolation And Otc Constructionmentioning
confidence: 99%
“…4 A recent study also reported that miR-145 regulates depigmentary activity through the suppression of MYO5A expression in mouse and human melanocytes. 5 As a critical transcriptional factor, MITF knockout affects many miRNAs expression profiles in melanocytes. 6 Therefore, the identification of MITF-targeted melanogenic miRNAs should give insight into the regulatory mechanisms of melanogenesis and provide new promising targets for depigmentation.…”
Section: Introductionmentioning
confidence: 99%